PEMBUATAN LOGO DAN KEMASAN KEPADA PELAKU USAHA GULA MERAH DAN NIRA KELAPA SAWIT SEBAGAI UPAYA MENINGKATKAN NILAI PENJUALAN - Elysa Rohayani Hsb, Dini Hariyati Adam, Mila Nirmala Sari Hasibuan, Lily Rohanita Hasibuan, Ali Akba (PT.JNDI, JURNAL BIMA, 2024)
Economic development of each village is very necessary to improve community welfare. Business actors have an important role in improving the economy of a village. That is Pulo Padang Village is a village located in Rantau Utara sub-district. It has significant potential in increasing the economic value of the community in Pulo Padang village. This service, carried out by the Community Service Team in the village of Pulo Padang sub-district, aims to provide education about making logos (brands) and packaging to business owners of brown sugar made from palm sap with the aim of increasing maximum sales value. Based on the results of Community Service carried out when carrying out community service, it was found that business actors of brown sugar made from palm sap as raw material do not have a logo (brand) and the packaging is not optimal as it should be. The methods used are observation, interviews, problem identification and final results. The final result of this service is the creation of a logo (brand) and brown sugar packaging.